(3HgLI GdEfSGf aj egLI GdMjhGfs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdeqdG GdgQhj GdbGQj , J (B1014 (3g` s; (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi cQe fhY GdEfSGf gPg QSGdI ajgG SdGdI eYQaI GdMjhGfGJ s
(3BNQgG (B:s
(3hbO EJab NJe gPG GdHGH ef BNQ GdcJGH HPcQ GdNdaGA dNGJe GdCfHjGA hcGf aQGZ eUfag efg efJUa TgQ QeVGf s
(3PcQ ajg eGLGA ai GdMjhGfGJ ef GdMGOjK GdfHhjI hGdCMcGe GdabgjI hGdJYQjaGJ GddZhjI hZjQ Pdc hdYdg GNJUQ ajg cJGH MjGI GdMjhGf ddOejQis
(3cJHJ fbdkG Yf fSNI GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B65 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B178s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B20 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs